Insights into Clinical Pharmacy Program in Iraq: Current Trends and Upgrading Plans - Al-Taie, Anmar (Jordan Journal of Pharmaceutical Sciences, 2020)
Clinical pharmacy is a patient-centered health practice in which the pharmacists work in collaboration with other healthcare providers for better treatment outcomes and improved patients’ quality of life. The introduction of clinical pharmacy as a remarkable health science discipline has necessitated a change in the curriculum of pharmacy education. The changes include, in addition to the curriculum, the introduction of several clinical pharmacy programs and professional practice-based models. This commentary highlights an overview upon the current trends in clinical pharmacy curriculum and practice in Iraq. The current clinical pharmacy curriculum in the academic platform is well designed and implemented alongside the currently introduced clinical pharmacy training programs. However, there is still a need to upgrade the entire pharmacy curriculum in the country in order to direct pharmacy profession towards more responsible and effective provision of direct patient care in Iraq.